Border Effect in Iberian Interregional Trade - Mourato, Joaquim; Ferreira, Ricardo Carvalho Bruno (My University, 2011)
Regardless of their formal existence, borders do have an effect of diminishing trade. The reduction that the existence of a border causes on potential trade flows is classified as “border effect”. The present paper provides an estimation of such effect on the Portugal -Spain border. For this, interregional trade relations are considered. All 20 peninsular NUTII regions are concerned. Data used are the interregional Iberian trade matrices provided in Ferreira (2008). A model for these flows is conducted using, among several other explaining factors, the existence of a national border between regions. Thus the border effect is predicted. On this paper we provide an estimation of border effects by economic sectors, showing that different industries experience in different manners the consequences of borders
Keywords: border effect; interregional trade; Portugal; Spain